Pemberdayaan UMKM Melalui Pelatihan Digital Marketing - Anugrah, Rinasa Agistya; Raharjo, Nibrasirizal Nirwasita; Agustin, Anindita Dwi Saphira; Pangestu, Rian Ade; Archita, Sylphie Cinta; Tsalistalitha, Syifa; Fadila, Fitri; Purwanto, Kevin Bintang Azhari; Kayana, Bajra Hita; Dhiyaulhaq, Raya Diaz Tahta (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2025)
Economic development continues to change along with the progress of the times, and MSMEs have a very crucial role in strengthening the foundation of a sustainable economy. This training program was implemented based on the results of observations showing that MSME actors in Segajih Hamlet are still limited in utilizing digital technology to develop their businesses. The purpose of this training is to provide the knowledge and skills needed to optimize the use of social media and other digital platforms, so that MSMEs in Segajih Hamlet can compete more effectively in an increasingly globally connected market. This community service method uses training and mentoring. Training and mentoring include several stages, namely preparation, organization, implementation, and evaluation, which focus on marketing through social media platforms such as Facebook, Shopee, and TikTok Shop. The results of the study conducted after the mentoring showed a significant increase in the understanding and application of digital marketing strategies among MSME actors by 33%, Then for the KWT Market Reach of Segajih Village there was an increase of 125%, Then also for information related to MSMEs in Segajih Village there was an increase of 67%. The increase has a positive impact on the increasing number of buyers at the KWT Market in Segajih Hamlet, which initially only had 15 buyers to 71 buyers. With digitalization, MSMEs in Segajih Hamlet have not only become better known, but have also been able to expand their market reach more effectively, so that they can increase their competitiveness and business sustainability in the global market, and strengthen their contribution to the local and national economy. In addition, the implementation of digital marketing allows MSMEs to be more flexible and adaptive to rapid market changes, and gives them the opportunity to innovate and increase their competitiveness in the increasingly advanced digital era